2001
DOI: 10.1002/gcc.1154
|View full text |Cite
|
Sign up to set email alerts
|

Methylation pattern of different regions of the MLH1 promoter and silencing of gene expression in hereditary and sporadic colorectal cancer

Abstract: Nonrandom, widespread promoter methylation of tumor suppressor genes is a common mechanism of gene inactivation during tumorigenesis. We examined the methylation status of two distinct regions of the MLH1 promoter (proximal and distal to the transcription start site) and the MLH1 gene expression by methylation-specific PCR and immunohistochemistry. A total of 72 colorectal tumors, both with (n = 51, 22 affected by hereditary nonpolyposis colorectal cancer, HNPCC, defined according to the international clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 13 publications
3
34
0
Order By: Relevance
“…Other investigators, conversely, have demonstrated decreased incidence of MLH1 methylation in the Lynch syndrome (0-23% vs. 54% in our study), [44][45][46][47][48] and a similar methylation rate in sporadic colon adenomas (1.1% vs. 0-4% in our study). 49 Differences in methylation rates between the aforementioned Lynch syndrome studies and the current study might reflect ascertainment biases related to entry selection criteria (e.g.…”
Section: Discussionsupporting
confidence: 75%
“…Other investigators, conversely, have demonstrated decreased incidence of MLH1 methylation in the Lynch syndrome (0-23% vs. 54% in our study), [44][45][46][47][48] and a similar methylation rate in sporadic colon adenomas (1.1% vs. 0-4% in our study). 49 Differences in methylation rates between the aforementioned Lynch syndrome studies and the current study might reflect ascertainment biases related to entry selection criteria (e.g.…”
Section: Discussionsupporting
confidence: 75%
“…Methylation of the latter region has been shown in the normal mucosa of patients with colorectal cancer (Kuismanen et al, 1999;Menigatti et al, 2001;Miyakura et al, 2001;Nakagawa et al, 2001;Kawakami et al, 2006). It does not per se affect hMLH1 transcription, but it has been shown to be the starting point for progressive methylation (Deng et al, 1999;Menigatti et al, 2001;Miyakura et al, 2001;Nakagawa et al, 2001) that spreads toward the transcription start site and eventually does silence expression of this mismatch repair gene (Deng et al, 1999;Miyakura et al, 2001;Nakagawa et al, 2001;Truninger et al, 2005;Capel et al, 2007). Involvement of the distal promoter thus reflects the earliest stage of this process, and as such, it is more likely to be observed in the normal mucosa of participants who have no apparent colorectal disease.…”
Section: Resultsmentioning
confidence: 99%
“…9 Promoter methylation has been demonstrated to inhibit hMLH1 protein expression. 25 So far, MSI-H cancers have been diagnosed by MSI testing using a panel of consensus MSI markers. 21 By definition, tumors with band shifts in 30-40% or more of the tested MSI markers are scored as MSI-H.…”
Section: Discussionmentioning
confidence: 99%
“…Methylation specific PCR (MSP) appears to be the method of choice to reliably study the methylation status of different gene promoters. 7,25 Several studies proved that methylation of the hMLH1 promoter strongly correlates with the loss of its protein expression. Despite the use of all these methods to distinguish MSI-H cancers from other sporadic CRCs, there is no consensus opinion as to which strategy would be most specific and efficient for defining the MSI-H phenotype.…”
Section: B I O S C I E N C E N O T F O R D I S T R I B U T I O Nmentioning
confidence: 99%